(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Early mobilization in the intensive care unit (ICU) is an integral part of physiotherapy-led rehabilitation, however it remains difficult to objectively and consistently monitor patient mobility given that current practice is limited by intermittent clinical assessment and electronic health record (EHR)-based documentation. Wearable sensors are an objective and scalable approach to mobility assessment in the critically ill. To assess the validity; efficacy and clinical usability of accelerometry based wearable sensors to monitor mobility profiles in ICU patients from a physiotherapy standpoint. A prospective observational study design was used. Triaxial wearable accelerometers were applied on standardized locations on the body of adult ICU patients. Mobility features derived from the sensors such as activity count, transitions of posture and ambulation events were continuously recorded. This information was verified by direct observation, and contrasted with standard EHR documentation of mobility. We computed sensitivities, agreement measures and regression models to quantify the association between mobility levels as covariates in state-outcome pairings. Wearable sensors had high validity for detecting mobility activities important to ICU care, and superior sensitivity compared to EHR documentation. More independently objectively measured mobility was associated with a shorter ICU LOS and a higher discharge functional status. Wear time of the device and completeness of recording were (very) high, indicating feasibility in the general ICU. Wearable sensors delivers a valid, objective and clinically useful measure of mobility in ICU patients. Incorporated into daily physiotherapy practice they may assist in optimizing early mobilization interventions, provide decision-making structure and potential resource allocation to patient care in the critical care setting.